Factors Associated With Patient Satisfaction in Outpatient Department of Suva Sub-divisional Health Center, Fiji, 2018: A Mixed Method Study - Swastika Chandra; Paul Ward; Masoud Mohammadnezhad (Frontiers Media S.A., 2019)
Background: With evolving health care industry toward patient centered orientation, inputs from the patients' perspective is valuable. Improved patient satisfaction is associated with increased levels of adherence to treatment processes and recommended prevention, and improved health outcomes. Hence, this study was conducted to assess the current level of patient satisfaction and explore its determinants in the Suva Subdivision health centers, Fiji, 2018.Methods: This was a mixed method cross-sectional study employing both quantitative and qualitative designs. A random sample of 410 participants attending the outpatient services completed the self-administered structured questionnaire. The questionnaire focused on socio-demographic features, waiting time, doctors' communication, and patient trust. Data from 375 questionnaires (response rate of 91%) was analyzed in SPSS where descriptive analysis and univariate and multivariate logistic regression was done at 0.05 level of significance and 95% confidence interval to find the determinants of patient satisfaction. From these 375 participants, 20 participants were purposefully selected for audio recorded interview guided by a semi-structured questionnaire and data was analyzed using thematic analysis.Results: The majority of the patients were generally fully satisfied with their consultation (69.3%). Univariate logistic regression showed that age, gender, education level, waiting time, doctors' communication behavior, and patient trust level were significantly associated with patient satisfaction independently. After controlling for all the variables, gender, number of visits, waiting time, and patient trust were significantly associated with trust. Those who had full trust in the doctors, were more likely to be fully satisfied with their consultation (aOR of 18; p = 0.0001) and those who got seen within 1 h, were more likely to be satisfied with their consultation (aOR of 3.3; p = 0.0001). Though, the patients voiced that getting a satisfying consultation was worth the wait. The doctors' attitude and way of communication also made a difference to the patient's level of satisfaction.Conclusions: This study showed that patient satisfaction is positively associated with patient trust, doctors' interpersonal skills and communication behavior and negatively associated with waiting time. Hence, doctors upgrading their communication skills and health service managers strategizing ways to improve waiting time can contribute to better patient trust and thus lead to better patient satisfaction and positively influence health outcomes.